PEMBERDAYAAN TANAMAN OBAT KELUARGA (TOGA) UNTUK MENGATASI HIPERTENSI DAN KOLESTEROL DI DESA GUDANG HIRANG RT 07 - Melviani Melviani; Syafira Nabillah; Aisyah Inayati; Siti Nurintan Fakhriah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Family Medicinal Plants (TOGA) are plants that are very efficacious, especially in the health sector. Based on data collection on disease complaints experienced by the community in Gudang Hirang Village Rt 07, 50% stated that they had hypertension and 33% suffered from cholesterol. The purpose of this activity is to increase knowledge to the people of Gudang Hirang Village Rt 07 about the types of family medicinal plants that can be used to control hypertension and cholesterol. The cadre of TOGA planting was carried out to the community by using ginger and celery plants. Ginger plants have many benefits, especially overcoming hypertension and strengthening the human immune system. While celery can be efficacious as a cholesterol treatment because it can reduce total cholesterol levels in hypercholesterolemia. The method used is a direct training method where the target is community representatives of Gudang Hirang Village Rt 07. The results of the activity show very high enthusiasm of cadres in increasing knowledge about the treatment of hypertension and cholesterol using medicinal plants ginger and celery. Thus, it is hoped that the education provided can be applied as an alternative to overcome public health problems.